2019
DOI: 10.1038/s41598-019-42388-3
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Position Moderates the Relationship between Late-life Depressive Symptoms and Memory Differently in Men and Women

Abstract: Late-life depression has been considered to be associated with memory deficits and hippocampal volume reduction. Considering that not all depression patients undergo the same amount of cognitive impairment or regional brain volume loss, moderating factors such as complex mental activity and social activity have been examined to assess whether these factors attenuate the detrimental impact of depressive symptoms on cognitive function and regional brain volume. However, the premise that a cognitively stimulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…It was confirmed that partic-ipation in social activities has the effect of delaying cognitive decline in the older adults 65 or older [28], and that the social activity indirectly affects cognitive function [29]. Furthermore, it has been found that consistent social engagement leads to cognitive improvement and the role in social networks and social activity moderates the relationship between depression and memory [30]. Therefore, it can be seen that the previous studies support these results by confirming that social activity is a significant factor that can prevent cognitive decline.…”
Section: Discussionmentioning
confidence: 79%
“…It was confirmed that partic-ipation in social activities has the effect of delaying cognitive decline in the older adults 65 or older [28], and that the social activity indirectly affects cognitive function [29]. Furthermore, it has been found that consistent social engagement leads to cognitive improvement and the role in social networks and social activity moderates the relationship between depression and memory [30]. Therefore, it can be seen that the previous studies support these results by confirming that social activity is a significant factor that can prevent cognitive decline.…”
Section: Discussionmentioning
confidence: 79%
“…Bridging position refers to the position within a social network in which 1 person serves as the link between 2 other people who are not connected to each other directly (ie, positive bridging status). [61][62][63] Occupying this position might benefit the individual's mental health by providing more opportunities for social contact and stability of the social network because of the heterogeneity of group. However, the bridging position may lead to greater psychological costs when the 2 parties not connected to each other have different (or even conflicting) social backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…57 Conversely, another study noted that, for women, being in a bridging position could require more psychological resources, while providing less fulfilling social support. 33,62 The difference between sexes with respect to the effects of bridging potential on perceived social support could also be explained by the differences in position that men and women have in social relationships. The above results thereby suggest that a large social network size or the presence of bridging potential should not be regarded as equivalent to greater social support in women.…”
Section: Discussionmentioning
confidence: 99%
“…For social networks, Turetsky et al [83] showed that psychological interventions can strengthen the connections of peer social network in terms of node degree, closeness, betweenness, etc. Morelli et al [235] studied how psychological traits correlate to centrality in social networks, and concluded that people high in wellbeing are central to the "fun" networks, while people high in empathy are central to the "trust" networks. Kim et al [236] showed that occupying a bridging position in a social network may alleviate the impact of depressive symptoms among older men, whereas the opposite holds true for older women.…”
Section: A21 Symbol-based Representationmentioning
confidence: 99%